KODE MALAIKAT DALAM NOVEL “NAIB IZRAIL” DAN “KAU MEMANGGILKU MALAIKAT”: SEBUAH BANDINGAN - Drei Herba Ta'abudi (Alfaz (Arabic Literatures for Academic Zealots), 2019)
This paper aims to compare “Malaikat” representations in the novel "Naib Izrail" (NI) by Yusuf As-Siba'i and "Kau Memanggilku Malaikat" (KMM) by Arswendo Atmowiloto. To parse the representation, this research uses a descriptive-interpretative method with Roland Barthes's five-code theory. Barthes's narrative theory is a theory that is close to the tradition of post-structuralism that is a theory that does not have an orientation towards a single meaning but instead aims to bring up a plurality of meanings. The results of this study show that there are manifestations of five codes from angelic representations in both novels. In addition, reading the representation of angels with the theory of five codes also shows a more meaningful meaning, namely by presenting a plurality of meanings by accommodating various dimensions in narrative analysis.